The Development of 5G Technology and Its Implications For The Industry - Elan Maulani, Isma; Amalia Johansyah, Citra (Devotion : Journal of Research and Community Service, 2023)
The development of 5G technology is very important in today's technological world. These technologies are bringing about significant changes in the way we interact with the digital world and are changing the way we use technology. The speed offered by 5G technology makes it possible to carry out data transfers very quickly, opening up opportunities for new applications and services in various sectors. The implications of the development of 5G technology on industry are huge and can affect various aspects, such as productivity, efficiency, and innovation. In the production sector, 5G technology makes it possible to speed up the production process and increase efficiency by using industrial technology 4.0. Within the service sector, 5G technology makes it possible to provide faster and high-quality services, such as more stable and faster video streaming services. On the other hand, the development of 5G technology also carries implications that must be considered, such as security and privacy issues. The speed offered by 5G technology makes it easier to carry out attacks and access personal data. Therefore, it is important for the industry to ensure that the 5G technology used meets the established security standards. The development of 5G technology brings significant changes in the industry and opens up new opportunities in various sectors. The implications of the development of 5G technology are huge and affect productivity, efficiency, and innovation. However, it is important for the industry to ensure that the 5G technology used meets established security standards to avoid security and privacy concerns.